Pendampingan Pelatihan Penerapan Teknologi Online Learning Pada Pesantren-Pesantren Menuju Pesantren Sadar Transformasi Pendidikan Di Era Revolusi Industri 4.0 - Mursidah Mursidah; Inuddanis Ikhwan Meranti (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
Islamic boarding schools are one of the traditional education institutions that have a thick culture in accordance with Islamic traditions. However, along with the development of science, information and communication technology should encourage pesantren to open up and modernize the traditional learning model towards modern learning. This is pursued as a step for pesantren in supporting digital-based learning performance. In achieving this step, Pondok Pesantren Manbaul Ulum Muncar Banyuwangi held service activities to provide online learning media training assistance as a first step to support the readiness of the Asatidz Teachers and Council in the cottage environment and delegates from the surrounding cottages. This activity is carried out in the form of training for teaching staff to prepare learning materials or media using Google Classroom media, Zoom, Google Meet. As well as training the teaching staff to be creative with interesting learning media such as using videos, the Powtoon application. And learning outcome evaluation models with interesting media such as Quizziz and Kahoot Applications. It is hoped that through this activity, the teaching staff will be motivated and able to develop slick learning in accordance with current advances in technology and information. And learning outcome evaluation models with interesting media such as Quizziz and Kahoot Applications. It is hoped that through this activity, the teaching staff will be motivated and able to develop slick learning in accordance with current advances in technology and information. And learning outcome evaluation models with interesting media such as Quizziz and Kahoot Applications. It is hoped that through this activity, the teaching staff will be motivated and able to develop slick learning in accordance with current advances in technology and information.